1991
DOI: 10.1002/mcs.1220030506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular shape recognition of polycyclic aromatic hydrocarbons with a liquid‐crystal bonded phase in supercritical fluid chromatography

Abstract: Abstract. The chromatographic characteristics of a liquid crystal bonded phase have been evaluated for the separation of polycyclic aromatic hydrocarbons (PAHs), especially focusing on its shape recognition capability in supercritical fluid chromatography (SFC). The results clearly indicate that the phase has a stronger molecular planarity and shape recognition capability than typical polymeric and monomeric octadecylsilica (ODs) phases because of the very ordered bonded phase structure. The recognition capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Mulcahey et al included PAHs in their review of the uses of SFC in the environmental field (192). Jinno et al compared the PAH molecular shape recognition properties of liquid crystal-bonded phases in packedcolumn SFC and in HPLC (214). They found that selectivity was enhanced in SFC.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…Mulcahey et al included PAHs in their review of the uses of SFC in the environmental field (192). Jinno et al compared the PAH molecular shape recognition properties of liquid crystal-bonded phases in packedcolumn SFC and in HPLC (214). They found that selectivity was enhanced in SFC.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…Miniaturization of the column can be regarded as one of the key technology to effectively develop novel stationary phases in LC [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], where microcolumns of 0.53 mm i.d. or 0.32 mm i.d.…”
Section: )mentioning
confidence: 99%
“…A few LCP have already been used in SFC, but with glass [56 60] or packed [61,62] capillary columns. On packed steel columns planarity recognition is increased, as previously reported by Pesek and Williamsen [63], whereas length-to-breadth solute recognition is no more rigorously observed than in RP HPLC.…”
Section: Bonded Liquid-crystalline Polymersmentioning
confidence: 99%